Assessment of nitrate contamination and its factors in the urban area of Yogyakarta, Indonesia - Surya Damar Sasongko Putro; Wahyu Wilopo (Journal of Degraded and Mining Lands Management, 2022)
Population growth in urban areas increases rapidly due to improving economic conditions. However, this growth is not always followed by the addition of public facilities such as clean water facilities and sewage water system networks, especially in developing countries. There are still many people who use on-site sanitation systems that will cause groundwater pollution problems. In addition, many people in urban areas still depend on groundwater for drinking water. The quality of groundwater becomes an essential factor for this purpose. One of the common groundwater problems in urban areas is nitrate concentration. Therefore, this study aimed to determine the potential groundwater contamination, the primary source of nitrate contamination in groundwater, and their influencing factor in the study area. The research method used the Cl/NO3 ratio and Cl/Br ratio to determine the source of nitrate in the study area. The groundwater contamination potential was evaluated based on depth to the groundwater table, sorption capacity above the groundwater table, permeability, groundwater table gradient, and horizontal distance from the contaminant source. In addition, the total of family members, age of the settlement, the distance of the well from the septic tank, and groundwater table depth were correlated with nitrate concentration. The results showed that nitrate levels in the research area generally exceed the maximum drinking water limit by WHO, with the maximum concentration reaching 167 mg/L. The high concentration of nitrate in the groundwater is due to contamination. According to the diagrams of nitrate versus chloride and the Cl/Br ratio analysis, the primary source of groundwater nitrate contamination is a septic tank. The higher family member and age of the settlement have a positive correlation with increasing nitrate concentration. Besides, distance from the septic tank and depth of the groundwater table is negatively correlated with nitrate concentration.